Association of C-reactive protein and arterial hypertension - Patidar, Om Prakash; Bhargava, Ajay Kumar; Gupta, Deepak (International Journal of Advances in Medicine, 2017)
Background: Emerging evidence links inflammation to atherosclerosis. Although some study have suggested the role of inflammation in patients with arterial hypertension and coronary artery disease cases. Higher levels of C-reactive protein (CRP), a common, easily measured inflammatory marker for which clinical cut points have been recommended, have been prospectively associated with an increased risk of hypertension. However, the relationship of other inflammatory markers, other than CRP, with the risk of developing hypertension remains largely untested. The activation of the renin-angiotensin system (RAS) is primarily involved in the pathophysiology of hypertension and the development of CVD. In addition to its effect on BP, angiotensin II is also a proinflammatory mediator. Antagonism of the RAS may improve cardiovascular outcomes beyond BP control, by reducing vascular inflammation and remodeling. It is over all contribution in AH and CVD far from being understand. Present study aimed to examine whether CRP a marker and systemic inflammation, are associated with AH. Methods: One hundred cases of AH attending Jhalawar Medical College and Hospital, Jhalawar were included in the study and their CRP levels and lipid profile and other routine investigations were carried out by suitable standard methods. Results: We found about 48 % cases of AH were having elevated CRP levels. Conclusions: CRP levels are associated with future development of AH, which suggest AH due to atherosclerosis is in part of inflammatory disease concluded in present study.